The Experience of Living with Multiple Sclerosis during the COVID-19 Pandemic - Roozbeh Shirooyeh; Anahita Khodabakhshi-Koolaee; Leila Jouybari (Kerman University of Medical Sciences, 2024)
Background: Many studies have shown that psychological distress such as worries and anxiety is one of the causes of the development, recurrence, or exacerbation of multiple sclerosis (MS). This study aimed to explore the lived experiences of patients with MS during the COVID-19 pandemic.Methods: This qualitative study was conducted using an interpretive phenomenological approach. The participants were selected from patients with MS in Tehran, Iran who were members of the Iranian MS Society in 2021. The research sample included 19 patients with MS who were selected using purposive sampling. The data were collected using semi-structured interviews until the data were saturated. The collected data were analyzed using Van Manen's phenomenological approach, and the validity and truthfulness of the data were confirmed using the four criteria proposed by Lincoln and Guba.Results: Explication of the data revealed 22 subthemes and 5 main themes. The main themes identified were: Feeling of helplessness and fear of inadequacy in self-care, Economic concerns and financial problems, Ineffective interaction with family members, preoccupations and obsessions with the pandemic, and ambivalent and conflicting beliefs about others.Conclusion: The experiences of those affected by the pandemic were linked to personal and familial concerns, health issues, feelings of inadequacy in self-care, and economic difficulties. Additionally, participants were preoccupied with the pandemic and the social problems they faced. Gaining an understanding of these experiences can offer valuable insights to medical professionals, families of patients, and relevant organizations regarding the lived experiences of individuals with MS.